A questionnaire based study of the quality of life of children with cerebral palsy aged 4–12 years - Snehal, Isha; Kumar, Arvind (Indian Journal of Child Health, 2019)
Background: Cerebral palsy (CP) is an umbrella term used to describe a group of non-progressive, but often changing motor impairment syndromes due to heterogeneous causes. Aim: The primary objective was to study the quality of life (QOL) of children aged 4–12 years with CP. The secondary objectives were to determine the correlation between QOL and demographic and clinical aspects. Materials and Methods: CP QOL-child, an Australia based questionnaire was translated and culturally adapted to 45 items. The questionnaire was then retranslated into English to ensure content and concepts were maintained. 50 parent-child dyads were interviewed after training of the primary interviewer. The statistical analysis of the data was done using statistical package for the social sciences software using t-test and Spearman correlation test. Results: The mean QOL score was within the “happy” range (66.38±10.38). The highest score was in “participation” and lowest in “special equipment.” Negative correlation was found in age with caregiver’s health (“your health”) and socioeconomic (SE) status with “others.” There was a positive correlation of paternal literacy with “communication,” “special equipment,” and “your health,” and “negative correlation of the number of siblings with others.” There was a negative correlation of gross motor classification system classes with “health” and manual ability classification system classes with mean QOL scores, “participation” and “health.” Conclusions: Increased access to special equipment is likely to help in improving QOL. There should be adequate support for the physical and mental health of parents and caregivers as well. Furthermore, caregivers must be educated and must be made aware of the disease. Comorbid conditions other than the primary disorder should not be ignored.